Returns to public agricultural spending in the cocoa and noncocoa subsectors of Ghana - Benin, Samuel (2017)
Using public expenditure and agricultural production data on Ghana from 1961 to 2012, this paper assesses the returns to public spending in the agricultural sector, taking into consideration expenditures on agriculture as a whole and then separately for expenditures in the cocoa versus the noncocoa subsectors. Different regression methods and related diagnostic tests are used to address potential endogeneity of agricultural expenditure, crosssubsector dependence of the production function error terms, and within-subsector serial correlation of the error terms. The estimated elasticities are then used to calculate the rate of return to expenditures in the sector as a whole and within the two subsectors. The elasticity of land productivity with respect to total agricultural expenditure is estimated at 0.33–0.34. For the noncocoa subsector, the estimated elasticity is 0.66–0.81. And in the cocoa subsector, it is 0.36–0.43. The returns to total agricultural expenditure are estimated at 82–84 percent for the aggregate analysis. For the disaggregated sectorial analysis, the returns to expenditure in the noncocoa subsector are estimated at 437–524 percent, whereas the returns to expenditure in the cocoa subsector are estimated at 11–14 percent. Implications are discussed for raising overall productivity of expenditure in the sector, as well as for further studies.